The role of the internal audit function (IAF) in integrated reporting and possible challenges and barriers to internal audit’s involvement - Engelbrecht, Lindie (My University, 2017)
The purpose of this research is to explore the roles of the internal audit function (IAF) in integrated reporting and identify the possible challenges and barriers to internal audit’s involvement. The research was conducted to fulfill three main purposes: to determine if the IAF has any role to play in integrated reporting; to identify the potential challenges and barriers of internal audit’s involvement; and to identify and recommend best practices for internal audit’s involvement. The potential roles of the IAF in integrated reporting is predicted through current practices and literature. The research approach required an understanding and contextualisation of current practices by interviewing Chief Audit Executives (CAEs), following a qualitative approach within an interpretivist paradigm. The results were analysed using a data analysis spiral.The main conclusion drawn was that the involvement of the IAF in integrated reporting is closely linked to the maturity of the integrated reporting process. The research sample consisted of CAEs of listed companies that are recognised as producing good integrated reports and whose integrated reporting processes are in varying stages of maturity. The practical implications for CAEs are to apply best practices in becoming involved in the integrated reporting process and to avoid potential challenges and barriers. The role of the IAF in integrated reporting has not yet been identified through prior studies and this can be considered as the most significant contribution of this study. Key words – Assurance, Integrated reporting, Internal audit
A research report submitted to the faculty of Commerce, Law and Management at the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Commerce (Accountancy), February 2017
Keywords: Auditing, Internal; Corporate governance; Corporations--South Africa--Accounting